2016
DOI: 10.1016/j.ijpharm.2016.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Novel high/low solubility classification methods for new molecular entities

Abstract: This research describes a rapid solubility classification approach that could be used in the discovery and development of new molecular entities. Compounds (N = 635) were divided into two groups based on information available in the literature: high solubility (BDDCS/BCS 1/3) and low solubility (BDDCS/BCS 2/4). We established decision rules for determining solubility classes using measured log solubility in molar units (MLogSM) or measured solubility (MSol) in mg/ml units. ROC curve analysis was applied to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 25 publications
1
28
1
Order By: Relevance
“…It is noteworthy that the mole-fraction solubility of ribavirin (II) in water at 298.15 K determined in this work is 0.01741, which is a little larger than 0.0103 (142 mgÁmLl À1 ) reported by Benet [19], Goodarzi [20], Dave [21] and Chen [22], 0.0109 (149 mgÁmL À1 ) reported by Vasa [23], and 0.0124 (169.99 mgÁmL À1 ) reported by Prasanthi [24]. The difference may be due to many factors, such as determination method, equilibration time, purity, sampling, analysis method and so on.…”
Section: Solubility Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…It is noteworthy that the mole-fraction solubility of ribavirin (II) in water at 298.15 K determined in this work is 0.01741, which is a little larger than 0.0103 (142 mgÁmLl À1 ) reported by Benet [19], Goodarzi [20], Dave [21] and Chen [22], 0.0109 (149 mgÁmL À1 ) reported by Vasa [23], and 0.0124 (169.99 mgÁmL À1 ) reported by Prasanthi [24]. The difference may be due to many factors, such as determination method, equilibration time, purity, sampling, analysis method and so on.…”
Section: Solubility Resultscontrasting
confidence: 54%
“…Due to its good properties, ribavirin has been received great attention. Nevertheless, in spite of the usefulness of this drug, the physicochemical properties of ribavirin in aqueous and organic solutions have not been studied systematically in the previous works [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Dave and Morris showed that the solubility classification could be evaluated using a 0.3 mg/mL cut-off, 25 , thus not requiring knowledge of the clinical dose, thereby allowing BDDCS classification to be made without knowledge of clinical dose (See Supplementary Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…Hosey and Benet 24 showed that based on in vitro permeability measurements, PPV for prediction of extensive metabolism were all 90% or greater. And most recently Dave and Morris 25 showed that they were able to correctly predict highly soluble vs. poorly soluble drugs using measured solubility parameters with greater than 85% probability. Thus as seen in Table 1, just knowing if a compound is BDDCS Class 2 prior to drug dosing has the ability to identify DILI potential with 90.2% PPV and 61.6% ACC.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfasalazine has a poor aqueous solubility, which is predicted to be 0.0024 mg/mL [25]. Preliminary tests in the current study showed that the drug solubility increased to 1 mg/mL, confirming that SSZ molecules interact with BSA.…”
Section: Preliminary Drug Release and Solubility Datamentioning
confidence: 50%